Narrativas de egressos de cursos de licenciatura na Rede de Aprendizagem e Desenvolvimento da Docência (ReAD) da UFSCar: caminhos e possibilidades formativas - Ferreira Filho, Antonio Carlos (Universidade Federal de São Carlos, 2023)
The theme of this study explores the experiences lived by graduates of teaching degree programs throughout their formative journeys in an online collaborative learning network called the Teaching and Development Learning Network (ReAD) between the years 2016 and 2019. ReAD brings together teaching degree students and teachers at different career stages, fostering intergenerational dialogue in formative activities, discussions, and the exchange of knowledge and experiences among participants. This investigation originated from the following guiding question: How do graduates of teaching degree programs analyze the experiences lived during their formative journey in the Teaching and Development Learning Network (ReAD), and how did these experiences contribute to their subsequent learning and professional practices? The research was conducted using a qualitative approach, and data were collected through online questionnaires, digital narratives written in ReAD, and online narrative interviews. The study involved 32 participants, with online narrative interviews conducted with 10 of them, highlighting recollections and reflections on their journeys in ReAD. The organization and analysis of the data were supported by Content Analysis, where we established an analysis axis consisting of four categories aligned with the research question and the general objective of the investigation: a) Motivations and expectations: the paths to ReAD; b) Recollections and reflections: teaching in ReAD's formative actions; c) Perspectives on teaching practice: experiences, challenges, and understandings after ReAD; d) Possibilities and potentialities of ReAD: participants' perspectives on their formative journeys. The results highlighted how participants carefully and maturely assessed their formative journeys in ReAD, reaffirming convictions about being a teacher and attributing new meanings to what was explored in the modules over time and through personal, professional, and academic experiences after ReAD. The results also revealed that, from the participants' perspective, formative actions contributed to their practical professional learning. Participants emphasized the activities carried out in ReAD aligned with the reality of teaching practice, as well as dialogues and sharing experiences with novice, experienced, and research-oriented teachers cooperatively in a professional socialization environment, conducive to teacher learning in a receptive manner with support and understanding of the dilemmas, feelings, and challenges of teaching. Furthermore, participants described ReAD as an innovative formative experience for learning about/for teaching. They pointed out the possibilities and potentialities of the activities conducted during the modules, as well as the distinctive nature of the intergenerational relationship established among participants at different stages of their teaching careers.
Graduates' narratives of teaching degree programs in the Teaching and Development Learning Network (READ) at UFSCar: formative paths and possibilities
Keywords: Egressos de licenciaturas; Aprendizagem da docência; Rede de aprendizagem online; ReAD; Narrativas de formação; Graduate teachers; Teaching learning; Online learning network; ReAD; Formation narratives; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO